Question Speech Act Produced by the Junior High School Students - Hendrayani, Kadek Nila; Tantra, Dewa Komang; Ramendra, Dewa Putu (International Journal of Language and Literature, 2023)
A question speech act is a communicative act that shows the intended language function, including questions, requests, apologies, suggestions, commands, and offers. This study aimed analyze the questions speech act types, question speech act social function, question speech act linguistics structure3 and questions speech act language elements produced by students in junior high school level. The study used descriptive qualitative. The subject of this study was seventh-grade students in junior high school. The data were collected through the elicitation technique. The analysis of this study included data collection, data reduction, data display, and conclusion drawing. The analysis result showed that from 960 questions, the students more frequently write two types of questions: yes/no questions and wh questions, rather than rhetorical questions and tag questions. The social functions used were directive functions speech act includes asking and requesting. The structure of yes/no questions was used verb in the beginning sentence then followed by the subject. Meanwhile, the structure of wh question was used wh then followed by an auxiliary verb, subject, and main verb. The result showed that non-effective questions were higher than effective questions, there were grammatical errors found that make the questions not effective. The language element of the questions speech acts based on the semantics situation types. The result showed that states is higher than activity, accomplishment, semelfactive and achievement.